Linking physiological state to movement dynamics in an open ocean predator, the blue shark (Prionace glauca) - Austin J. Gallagher; Evan B. Byrnes; Rachel A. Skubel; Brian Raymond; Joe Romeiro; Steven J. Cooke; Garrett M. Street; Neil Hammerschlag (PLoS ONE, 2026)
The movement behavior of open ocean fishes is challenged by metabolic demands resulting from sustained swimming and the availability of resources in a dynamic, ephemeral environment. Advances in electronic tagging and tracking technologies have permitted unprecedented opportunities to describe the movements of open ocean fishes in these environments, however, our understanding of the mechanistic drivers of individual variation in movement performance is limited. In this study, we tested the hypothesis that movement capacities of open ocean sharks would be related to physiology and body condition. We measured the physiological status (e.g., energy stores and body condition) of blue sharks ( Prionace glauca ) captured in the open ocean, and then tracked their movements over 45 days. We then explored for relationships between physiological metrics and individual differences in metrics of movement behavior (distance traveled, activity space, behavioral state, and tortuosity) of the tracked blue sharks. Analyses detected consistent positive relationships between individual plasma triglyceride concentrations and body condition (sampled at time of capture) on distance traveled, activity space, behavioral state, and tortuosity - up to 45 days post tagging, with models explaining up to 79% of individual variation in movement. These findings highlight the potential role of metabolic lipid reserves in shaping movement behavior of open ocean, predatory sharks in patchy, ephemeral environments. More broadly, they offer new insight into the factors which may influence individual variation in the timing and scale of movement in oceanic fishes.